The impact of digital platforms in tax administration services on local government tax revenues: evidence from Indonesia - Mujiyati Mujiyati; Zulfikar Zulfikar; Banu Witono; Ichsan Cahyo Utomo (Public and Municipal Finance, 2024)
In Indonesia, digital platforms in tax administration services have been implemented for more than a decade. This study aims to investigate whether digital platforms for motor vehicle tax administration services can increase local government tax revenues. Then, it is continued by testing the moderating role of motor vehicle tax revenue targets and online service information. Data were collected from the Unit Penerimaan Pendapatan Daerah (UPPD) Central Java – Indonesia. Observations focused on motor vehicle tax services carried out during the 2018–2022 period in 37 district and city UPPDs. The analysis uses GLS regression, which was developed with modeling regression analysis (MRA). The study results show that implementation of digital platforms in motor vehicle tax administration services can increase local government tax revenues. This relationship will be further strengthened if there are online information services, both circular and standby. Further investigation results revealed that relying on tax revenue targets to strengthen the relationship between digital platforms in tax administration services and local government tax revenues is not viable. AcknowledgmentThis study is supported by the Direktur Riset, Teknologi dan Pengabdian Masyarakat (DRTPM) based on decree number 108/E5/PG.02.00.PL/2024 and contract number 007/LL6/PB/AL.04/2024, 196.43/A.3-III/LRI/VI/2024.